Factors driving international technology transfer: Empirical insights from a CDM project survey - Carsten Gandenberger; Miriam Bodenheimer; Joachim Schleich; Robert Orzanna; Lioba Macht (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2015)
This study employs an original survey-based dataset to explore technology transfer in CDM projects. The findings suggest that about two-thirds of the CDM projects involve a medium to very high extent of technology transfer. The econometric analysis distinguishes between knowledge and equipment transfer and specifically allows for the influence of technological characteristics, such as novelty and complexity of a technology, as well as the use of different transfer channels. More complex technologies and the use of export as a transfer channel are found to be associated with a higher degree of technology transfer. Projects involving 2- to 5-year-old technologies seem more likely to involve technology transfer than both younger and older technologies. Energy supply and efficiency projects are correlated with a higher degree of technology transfer than non-energy projects. Unlike previous studies, our analysis did not find technology transfer to be related to project size, the length of time a country has hosted CDM projects or the host country' s absorptive capacity. Our findings are similar for knowledge and equipment transfer. CDM projects are often seen as a vehicle for the transfer of climate technologies from industrialized to developing countries. Thus, a better understanding of the factors driving technology transfer in these projects may help policy makers design policies that better foster the transfer of knowledge and equipment, in addition to lowering greenhouse gas emissions. This may be achieved by including more stringent requirements with regard to international technology transfer in countries' CDM project approval processes. Based on our findings, such policies should focus particularly on energy supply and efficiency technologies. Likewise, it may be beneficial for host countries to condition project approval on the novelty and complexity of technologies and adjust these provisions over time. Since such technological characteristics are not captured systematically by PDDs, using a survey-based evaluation opens up new opportunities for a more holistic and targeted evaluation of technology transfer in CDM projects.
urn:nbn:de:0011-n-3319694
Keywords: 330; Clean Development Mechanism; Technology Transfer; North-South; Energy Technology; Development and Climate